Numerosity discrimination in preschool children - Almeida, Alzira Rosa Carvalho de (2007)
We used a numerical bisection procedure to examine preschool children's sensitivity to the numerical attributes of stimuli. In Experiment I children performed two tasks. In the Cups Task they earned coins for choosing a green cup after two drumbeats and a blue cup after eight drumbeats. In the Gloves Task they earned coins for raising a red glove on their left hand after two drumbeats and a yellow glove on their right hand after eight drumbeats. Then in each task a psychometric function was obtained by presenting intermediate numerosities and recording the percentage of trials in which children chose the "many" option. In Experiment 2 children's performance in a '2 vs. 8' discrimination was compared with their performance in a "4 vs. 16" discrimination. Results showed that the individual psychometric functions were of two types, one in which the percentage of "many" choices increased gradually with stimulus numerosity and another in which it increased abruptly, in a step-like manner. Although the average point of subjective equality was close to the geometric mean of the anchor numerosities and the average functions for "2 vs. 8" and "4 vs. 16" superimposed when plotted on a common scale (the scalar property), the individual data were highly variable both across tasks (Cups and Gloves) and numerosity ranges (`2 vs. 8' and `4 vs. 16'). It is suggested that between-and within-subjects variability in the psychometric function is related to children's verbalizations about the sample stimulus.